Geodetski vestnik and its path to better international recognition - Koler-Povh, Teja (Geodetski vestnik, 2015)
The editorial board of Geodetski vestnik, the leading Slovenian scientific and professional journal in the fields of geodesy, land surveying, geoinformatics and land management, has taken many actions to increase the quality of the journal over the past decade. Among others, the reviewing procedures were improved by introducing doubleblind peer review of articles, internationalisation of editorial and review boards has been done, the journal has been included in several international bibliographic databases, and open access to full-text papers at the journals website since 2000 onwards has been provided. The main aim of the study has been to analyse the influence of editorial policy on the international recognition (citations) of Geodetski vestnik as well as on the quality of the literature cited in the journal. Citations of Geodetski vestnik in the period 2009-2013 are analysed in this article, based on the data from the WoS database. It has been shown that indexation in many information systems and databases, such as COBISS. SI, DOAJ, WoS, DRUGG and CrossRef, has increased the visibility of the journal and its articles at both national and international levels.
Keywords: citations of publications; citiranje; civil engineering; geodesy; geodezija; gradbeništvo; odprti dostop; open access; scientific publications; znanstvene objave